Growth and Structural Changes of Foreign Workers in Japan: Economic Implications for Sri Lanka - Karunaratne, H.D. (My University, 2012)
Although growth of foreign workers in Japan has been the lowest among the OECD countries, their structural changes in terms of country of origin, age, gender, profession, industry, size of the firm and types of works have significantly diversified during the past three decades. Total number of registered foreign workers in Japan increased from 260,000 in 1990 to 876,942 in 2003 by 237 percent. Out of this growth 86 percent was recorded by temporary workers. The share of Korean workers has been declining while workers came from China and other Asian countries have been increasing during the same period. Sri Lanka has been recording as one of the highest number of migrant sending countries to Japan during the past few years. The number of registered Sri Lankans in Japan increased from 1,206 people in 1990 to over 12,000 people in late 2006. By using available macro level data and sample survey of 100 Sri Lankan migrant workers in Japan this paper attempted to elaborate these relations.